Model Panel Bulu Ayam Sebagai Material Alternatif - Ansarullah, Ansarullah; Yusri Lukman, Muhammad; Budi, Andas; Juniar, Pratiwi; Musda, Gusti Hardyanti; Yudistira, Adithya (Forum Cendekia: Jurnal Ilmiah Multidisipliner, 2024)
Billions of chicken feather waste scattered in our neighborhood have not been utilized properly. This research is related to the processing and utilization of chicken feather waste into alternative materials in the field of architecture and can be utilized by the wider community. (1) Chicken feathers are waste from the results of chicken slaughtering in chicken slaughtering businesses or industries, the waste of which is quite large and can lead to waste pollution if it is not processed immediately.; (2) The purpose of this study is to process and utilize chicken feather waste into alternative materials in the field of architecture; (3) The method is experimental by forming models to create materials that can be used as alternative materials in buildings, and tests are carried out in the laboratory and involve 3 students.; (4) The results achieved are chicken feather waste can be formed into alternative materials as walls with a simple patent output that has been grantedhe